Productivity and economics of rice (Oryza sativa) - wheat (Triticum aestivum) cropping system as influenced by neem oil-treated urea and biogas slurry* - BHARDE, N M; SHIVAY, Y S; SINGH, S; KUMAR, D (The Indian Journal of Agricultural Sciences, 2011)
Rice (Oryza safiva L.)-wheat (Triticum aestivum L. emend. Fiori & Paol) cropping system in India is being cultivated on an area of 10.5 million ha which contributes approximately 25% in the national food grain production (Gupta 2003). Use of nitrogenous fertilizers, viz urea has played key a role in enhancing the rice-wheat production, yet its use-efficiency in rice is only 3040% or even less (Prasad and Power 1995)..............